Spatial Biodiversity of Birds in Land Covers of Wetlands on Jakarta’s North Coast - Andriwibowo; Basukriadi, Adi; Nurdin, Erwin (Universitas Atma Jaya Yogyakarta, 2023)
Wetlands are suitable habitats for the coastal bird community. One of the important wetlands is located on Jakarta’s North Coast. Here, this study aims to assess the spatial biodiversity of birds in various land covers of wetlands on Jakarta’s North Coast. In total, there were 23 species belonging to 12 bird families. Ardeidae, Rallidae, and Silviidae bird families have more species compared to other families. The biodiversity H' values in the wetlands dominated by mangrove cover were the highest, at 2.527, followed by the wetlands having less mangrove cover and more water bodies and fish ponds only having H’ values equal to 1.811. The arboreal, small-to-medium-sized birds belong to Nectariniidae, Ploceidae, Silviidae, and Dicaeidae were widely distributed across all land cover. In contrast, the wetlands characterized by mangrove cover dominance combined with muddy substrate coasts were dominated by mid-large water birds belong to Anatidae, Scolopacidae, Ciconiidae, Rallidae, Ardeidae, Phalacrocoracidae, Anhingidae, and Alcedinidae. It is recommended to protect the mangroves and reforest the wetlands with mangroves to provide more habitats for the coastal bird community.